Performance of CZTSSe thin film solar cells fabricated using a sulfo-selenization process: Influence of the Cu composition. (1st January 2018) - Chalapathy, R.B.V.; Gang, Myeng Gil; Hong, Chang Woo; Kim, Ji Hun; Jang, Jun Sun; Yun, Jae Ho; Kim, Jin Hyeok
Graphical abstract: Highlights: CZTSSe thin film solar cells were fabricated by sulfo-selenization of sputtered metallic Mo/Zn/Cu/Sn/Cu precursors. The surface composition of the absorbers was Cu depleted and Zn rich compared to the bulk of the absorbers. The ideality factors 'A' over 2 suggest that increased interface recombination in the devices which reduced the open circuit voltage of the devices. By tuning the Cu content in the absorbers solar cells with conversion efficiency about 8.03% was obtained. And the best efficiency of 8.17% was achieved without an antireflection coating. Abstract: In this work, earth-abundant CZTSSe thin film solar cells were fabricated by sulfo-selenization of the Mo/Zn/Cu/Sn/Cu metallic precursors. The influences of morphological and compositional properties of the absorbers on performance of solar cells were investigated by tuning Cu content in the films. The Raman analysis showed that absorbers consist of a kesterite CZTSSe phase with ZnSe as a minor secondary phase. X-ray photoelectron spectroscopy (XPS) analyses revealed that the surfaces are Cu depleted and Zn enriched compared with the bulk composition of the absorbers. The results indicate that during sulfo-selenization the Cu diffused into the film and the Zn towards the film surface. The performance of the solar cells initially improved with the increasing of the Cu content and then decreased. By tuning the Cu content in the absorbers, the minority-carrier life time improved from 0.8 to 1.6 ns. The power conversion efficiency increased from 5.1 to 8.03% with fine controlling of Cu composition of the CZTSSe absorbers. The diode-ideality factors are higher than 2, suggesting an increased interfacial recombination in the devices. The high ideality-factors A and low minority carrier life times may originate from surface and bulk related defects, which in turn limits the Voc and the achievable high conversion efficiency for the CZTSSe thin film solar cells.